A Comparative Study: ISA 1960, SOSMA 2014 and the Federal Constitution - Dhanapal, Saroja; Sabaruddin, Johan Shamsuddin (Journal of Malaysian and Comparative Law, 2015)
The Internal Security Act (ISA) 1960 was the preventive detention law in force in Malaysia prior to the enactment of the current preventive law, the Security Offences (Special Measures) Act, (‘SOSMA’) 2012. ISA 1960 was enacted after Malaysia gained independence from Britain in 1957. It allowed for detention without trial for criminal charges under limited, legally defined circumstances. On 15 September 2011, the Prime Minister of Malaysia, Dato Seri Najib Tun Razak said that this legislation will be repealed and replaced. The SOSMA 2012 was passed by the Parliament to replace the ISA 1960 and it was given the royal assent on 18 June 2012. Since the first Act came into play in 1960, there has been an ongoing debate as to its implication and necessity which the new Act has not laid to rest. Since its enactment, this new Act has been scrutinized and debated upon at various levels both locally and internationally. This research analyses the SOSMA 2012 to identify whether the new Act has removed all the concerns raised against the previous Act, the ISA 1960. It also aims to ascertain if any of the rights upheld in the Federal Constitution are being violated by the provisions in the new Act. The findings indicate that there is still room for concern on the implications of the Act in reference to infringement of the rights upheld in the Federal Constitution. However, these infringements can also be said to be in alignment with Article 149 of the Federal Constitution. The paper ends with a comment that it is too early to make any judgment be it positive or negative as the Act is still new and it has to run its course before any conclusion can be made.